Validity and reliability of a new field test (Carminatti's test) for soccer players compared with laboratory-based measures - da Silva, J. F.; Guglielmo, L. G. A.; Carminatti, L. J.; de Oliveira, F. R.; Dittrich, N.; Paton, C. D. (Journal of Sports Sciences, 2011)
The aim of this study was to assess the validity (Study 1) and reliability (Study 2) of a novel intermittent running test (Carminatti's test) for physiological assessment of soccer players. In Study 1, 28 players performed Carminatti's test, a repeated sprint ability test, and an intermittent treadmill test. In Study 2, 24 players performed Carminatti's test twice within 72 h to determine test-retest reliability. Carminatti's test required the participants to complete repeated bouts of 5 × 12 s shuttle running at progressively faster speeds until volitional exhaustion. The 12 s bouts were separated by 6 s recovery periods, making each stage 90 s in duration. The initial running distance was set at 15 m and was increased by 1 m at each stage (90 s). The repeated sprint ability test required the participants to perform 7 × 34.2 m maximal effort sprints separated by 25 s recovery. During the intermittent treadmill test, the initial velocity of 9.0 km · h-1 was increased by 1.2 km · h-1 every 3 min until volitional exhaustion. No significant difference (P > 0.05) was observed between Carminatti's test peak running velocity and speed at VO2max (v-VO2max). Peak running velocity in Carminatti's test was strongly correlated with v-VO2max (r = 0.74, P < 0.01), and highly associated with velocity at the onset of blood lactate accumulation (r = 0.63, P < 0.01). Mean sprint time was strongly associated with peak running velocity in Carminatti's test (r = -0.71, P < 0.01). The intraclass correlation was 0.94 with a coefficient of variation of 1.4%. In conclusion, Carminatti's test appears to be avalid and reliable measure of physical fitness and of the ability to perform intermittent high-intensity exercise in soccer players.